Molecular Detection and Genetic Characterization of Novel RNA Viruses in Wild and Synanthropic Rodents and Shrews in Kenya - Onyuok, Samson Omondi; Hu, Ben; Li, Bei; Fan, Yi; Kering, Kelvin; Ochola, Griphin Ochieng; Zheng, Xiao-Shuang; Obanda, Vincent; Ommeh, Sheila; Yang, Xing-Lou; Agwanda, Bernard; Shi, Zheng-Li (Frontiers in Microbiology, 2019)
The majority of emerging and reemerging zoonotic viral pathogens are RNA viruses. Pathogen discovery programs of emerging infectious diseases (EIDs) in wildlife have implicated rodents and shrews as hosts of diverse human pathogens, such as hantaviruses, arenaviruses, paramyxoviruses, etc. Despite these threats, little is known about the diversity of viruses circulating among rodents and shrews in Kenya, meaning the risk of infectious disease outbreak from these small mammals could be oblivious. This study reports the first surveillance towards understanding the diversity of RNA viruses carried by rodents and shrews in areas of high-potential contact with humans in Kenya through molecular detection. A total of 617 samples comprising fecal, urine and tissues from 138 rodents and 5 shrews were screened for 8 different families of viruses using RT-PCR assays. The results highlight the presence of diverse astroviruses, paramyxoviruses, hepeviruses and arenavirus, circulating in both wild and synanthropic Kenyan rodents and shrews. Most of the viruses detected in this study are novel strains and some belong to the families that contain important human viral pathogens. Notably, a novel arenavirus was detected in Grammomys macmillani, a rodent species newly identified to harbor arenavirus, and it potentially represent a novel arenavirus species. Our findings demonstrate the need for continued pathogen surveillance among these small mammals as well as among the vulnerable and exposed livestock and humans. This would help in development and implementation of effective preventive and control strategies on EIDs in countries with rich wildlife biodiversity like Kenya.